SEMUT (TENSES VERB MUTER) AS A MEDIA TO UNDERSTAND BASIC ENGLISH (TENSES AND VERB) FOR STUDENTS IN PLUMPANG TUBAN 1 MIDDLE STATE - Tyas Rahayu Kartika; Ratna Rahayu Nengseh; Nur Lujeng Kinanti; Eni Indria Safitri; Albrian Fiky Prakoso (Universitas Islam Nahdlatul Ulama Jepara, 2020)
This study aims to determine the results of the development of the media SEMUT (Verb Muter Tenses) with a series of learning media ERTE MAP (Preparation of Verb Words and Tenses) and a module entitled